Franklin Street, ca. 1855 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of houses lining the southside of Franklin Street between Hawley Street to the west and Devonshire Street to the east. A small park is located in the center of Franklin Street. Photographs